A VEXING RECURRENT PERICARDIAL EFFUSION WITHOUT UNDERLYING PATHOLOGY - SUBSEQUENT DIAGNOSIS OF LYMPHOMA PROVES A RARE FIRST PRESENTATION - Ur Rahman, Haseeb; Hasan, Saad; Hutchison, Stephen (Journal of Ayub Medical College Abbottabad, 2020)
An elderly man had recurrent admissions with large symptomatic pericardial effusions. Initial computed tomography (CT) of thorax, abdomen and pelvis and pericardial fluid analysis did not reveal underlying cause. On subsequent presentation, pericardial window was formed but repeat pericardial fluid analysis and biopsy failed to give a diagnosis again. He then presented approximately after four months with worsening symptoms of dyspnoea and weight loss. General physical examination at that point noted inguinal lymphadenopathy. Repeat imaging with CT and magnetic resonance imaging (MRI) showed features of metastatic malignancy. Tissue diagnosis from inguinal lymph nodes proved to be diffuse large B-cell lymphoma (DLBCL). Keywords: pericardial effusion; inguinal lymphadenopathy; diffuse large B-cell lymphoma